Developing a robust and sensitive analytical method to detect off‑flavor compounds in fish - Lindholm-Lehto, Petra (Springer, 2022)
In recirculating aquaculture systems (RAS), off-flavors that accumulate in fish muscle tissue can be problematic in terms of consumer acceptance and the reputation of farmed fish products. Although off-flavors are not toxic at low concentrations, they often give fish muscle earthy, muddy, or other unwanted flavors. Traditionally, muddy off-flavors caused by geosmin (GSM) and 2-methylisoborneol (MIB) have been detected, but a variety of other compounds and flavors have also been identified. In this study, a method based on solid phase micro extraction (SPME) coupled with gas chromatography and mass spectroscopy was developed to identify and quantify 14 off-flavor–inducing compounds in RAS–farmed fish. The selected off-flavors were quantified in circulating water and in fish from a pilot-scale RAS rearing rainbow trout (Oncorhynchus mykiss). The method showed high accuracy and precision with limits of detection and quantification at a low ng L−1 level. In this study, 13 compounds were found in the fish muscle which decreased in concentrations during the 15-day depuration period. This study showed that off-flavors in fish can also be induced by other compounds besides GSM and MIB. This emphasizes the need for sufficient off-flavor control in the RAS, but also the importance of an accurate and reliable analytical quantitation method.
Keywords: Depuration; Gas chromatography; Mass spectrometry; Method development; Off-flavors; Rainbow trout; Recirculating aquaculture system (RAS); Solid phase microextraction (SPME)